Comprehensive Investigation of the Adsorption, Corrosion Inhibitory Properties, and Quantum Calculations for 2-(2,4,5-Trimethoxybenzylidene) Hydrazine Carbothioamide in Mitigating Corrosion of XC38 Carbon Steel under HCl Environment - Mouats, Nadia; Djellali, Souad; Ferkous, Hana; Sedik, Amel; Delimi, Amel; Boublia, Abir; Benguerba, Yacine (Amer Chemical Soc, 2024)
This study investigates the inhibitory effects of 2-(2,4,5-trimethoxy benzylidene) hydrazine carbothioamide (TMBHCA) on the corrosion of carbon steel in a 1 M HCl solution across various concentrations. The assessment employs a comprehensive approach, combining gravimetric analysis, potentiodynamic polarization tests, and electrochemical impedance spectroscopy (EIS). Additionally, scanning electron microscopy (SEM) and quantum chemical calculations are employed to provide a thorough understanding of the corrosion inhibition mechanism. The influence of exposure time on mild steel corrosion is systematically examined. Results reveal a remarkable reduction in the corrosion rate of steel, with TMBHCA demonstrating its highest inhibition efficiency of 97.8% at 200 ppm. Potentiodynamic polarization studies characterize TMBHCA as a mixed-type inhibitor, while Nyquist plots illustrate increased charge transfer resistance and decreased double-layer capacitance with escalating TMBHCA concentrations. Consistency between weight loss measurements and electrochemical findings further validates the efficacy of TMBHCA as a corrosion inhibitor. SEM images substantiate and visually support the obtained results. An immersion test conducted at 25 degrees C over 28 days showcases a notable enhancement in TMBHCA efficiency (IE%) from 45.16% to 92.43% at 200 ppm as the immersion period progresses from 1 day to 28 days. This improvement is attributed to the augmented adsorption of inhibitor molecules on the steel surface over time. These comprehensive findings significantly contribute to our understanding of TMBHCA's corrosion inhibition behavior, emphasizing its potential as a highly efficient corrosion inhibitor for diverse industrial applications.
Keywords: Mild-Steel; Schiff-Bases; Molecular-Dynamics; Acid; Copper; Extract; Films; Temperature; Derivatives; Simulation